1985
DOI: 10.1111/j.1440-1754.1985.tb00119.x
|View full text |Cite
|
Sign up to set email alerts
|

Some factors influencing the stature of Dunedin 7 year old children: A report from the Dunedin Multidisciplinary Health and Development Research Unit

Abstract: The stature of 987 representative Dunedin 7 year olds was measured and some factors contributing to stature were studied in 666 children for whom complete data were available. Dunedin children were of similar stature to American children but were about 1 cm taller than British children. Socio-economic stature (SES), birth weight and maternal stature were significantly correlated with stature, while the sex of the child, gestational age, maternal age, ordinal position of the child in the family and number of ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
2

Year Published

1987
1987
2018
2018

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 4 publications
2
14
2
Order By: Relevance
“…Although in our study, effect on height was not significant statistically, Peck and V å ger ö showed that children from larger families tend to be shorter than small families [17]. But some British studies showed that the family size-height relationship is not linear correlation with growth [18]. Silva and et al determined the effect of socio-economic factors and birth weight on growth of children.…”
Section: Discussioncontrasting
confidence: 56%
See 2 more Smart Citations
“…Although in our study, effect on height was not significant statistically, Peck and V å ger ö showed that children from larger families tend to be shorter than small families [17]. But some British studies showed that the family size-height relationship is not linear correlation with growth [18]. Silva and et al determined the effect of socio-economic factors and birth weight on growth of children.…”
Section: Discussioncontrasting
confidence: 56%
“…Silva and et al determined the effect of socio-economic factors and birth weight on growth of children. Their result revealed that socio-economic status and birth weight were significantly correlated with stature, while the sex of children, maternal age, size of family, and ordinal position of the child in the family were not significantly related to each other [18]. Although most of our samples were in normal range of BMI generally deficiency was revealed more in high risk groups.…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…10 In many similar developed-country cities, adults now in their middle age will have also experienced their greatest lead exposures during childhood. 3,12,13 In addition, this study was observational and correlational, and therefore does not establish a causal relation between lead exposure and outcomes, such as would be the case in a hypothetical experiment with children randomly assigned to lead exposure.…”
Section: Discussionmentioning
confidence: 99%
“…Subscales of antisocial, neurotic, hyperactive, and inattentive behaviour problems were derived by summing the relevant items from these behaviour questionnaires according to established derivations 910 Cognitive tests included verbal and non-verbal intelligence quotient (IQ) at 11 and 13 years (using the WISC scale12), the Dunedin spelling tests at 11 and 13 years,13 and the Burt reading test14 at 11, 13, 15, and 18 years. The Burt reading test was used up to age 18, as cohort members were already familiar with the test and it has been shown to be a reliable and valid index of reading ability 14.…”
Section: Methodsmentioning
confidence: 99%